Welfare Gains from the Variety Growth - d'Artis Kancs; Damiaan Persyn (Publications Office of the European Union, 2019)
We estimate the variety gains of trade in Estonia, Latvia and Lithuania following the fall of the iron curtain more than a quarter of a century ago. We apply the methodology of Feenstra (1994); Broda and Weinstein (2006); Ardelean and Lugovskyy (2010) and Soderbery (2015) to domestic and international trade data for the period 1988-1997. Although, there was a decline in the number of local varieties during this period, an increase in the number of import varieties from the EU more than outweighed this decline. The increasing variety of imported goods from EU countries substantially lowered the cost of living, resulting in welfare gains to consumers that range from 0.73% in Latvia to 1.28% of GDP per year in Estonia.
Keywords: C68; F12; F14; F17; R12; R23; 330; variety growth; welfare gains; trade integration; iron curtain